Programmed Death Ligand 2 in Cancer-Induced Immune Suppression - Esdy N. Rozali; Stanleyson V. Hato; Bruce W. Robinson; Richard A. Lake; W. Joost Lesterhuis (Clinical and Developmental Immunology)
Inhibitory molecules of the B7/CD28 family play a key role in the induction of immune tolerance in the tumor microenvironment. The programmed death-1 receptor (PD-1), with its ligands PD-L1 and PD-L2, constitutes an important member of these inhibitory pathways. The relevance of the PD-1/PD-L1 pathway in cancer has been extensively studied and therapeutic approaches targeting PD-1 and PD-L1 have been developed and are undergoing human clinical testing. However, PD-L2 has not received as much attention and its role in modulating tumor immunity is less clear. Here, we review the literature on the immunobiology of PD-L2, particularly on its possible roles in cancer-induced immune suppression and we discuss the results of recent studies targeting PD-L2 in cancer.